2003
DOI: 10.1089/104454603322572697
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Induced Neutropenia in Children: Management with Lithium Carbonate

Abstract: Clozapine, an atypical antipsychotic, is the most effective medication for treatment-resistant schizophrenia, but its use is limited by the high risk of neutropenia and agranulocytosis. In children, the rate of clozapine-induced neutropenia is even higher than in adults. We report two cases of children 7- and 12-years old diagnosed with very early onset schizophrenia, who developed neutropenia when treated with clozapine. In both cases addition of lithium carbonate elevated the white blood count (WBC) allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…The incidence of neutropenia in this study was higher than 7.4% at 1 year (Kang et al, 2006) reported for general Korean population, supporting previous concerns that clozapine-induced neutropenia may be more common in children and adolescents compared to adult population (Gerbino-Rosen et al, 2005;Kennedy et al, 2007;Sporn et al, 2003). The reported incidence of clozapine-induced neutropenia in children and adolescents vary from 8% (Gogtay and Rapoport, 2008) up to 50% (Kennedy et al, 2007) and the cumulative risk of hematological event at 1 year of clozapine treatment was reported to be 16.1% (Gerbino-Rosen et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of neutropenia in this study was higher than 7.4% at 1 year (Kang et al, 2006) reported for general Korean population, supporting previous concerns that clozapine-induced neutropenia may be more common in children and adolescents compared to adult population (Gerbino-Rosen et al, 2005;Kennedy et al, 2007;Sporn et al, 2003). The reported incidence of clozapine-induced neutropenia in children and adolescents vary from 8% (Gogtay and Rapoport, 2008) up to 50% (Kennedy et al, 2007) and the cumulative risk of hematological event at 1 year of clozapine treatment was reported to be 16.1% (Gerbino-Rosen et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…However, this one patient did show some evidence of masking of the neutropenia by lithium. Successful use of adjunctive lithium has also been reported in two children aged 7 and 12 years, respectively, diagnosed with very early onset schizophrenia and who developed neutropenia when treated with clozapine (Sporn et al, 2003). Lithium is an inhibitor of myeloperoxidase (Anderson et al, 1982;Gomez-Estrada et al, 1984;Turkozkan et al, 1993), which may explain its protective effect on clozapine-induced neutropenia, at least in part.…”
Section: Clozapine and Neutropeniamentioning
confidence: 97%
“…We could not introduce the available antipsychotics (thioridazine, chlorpromazine, clozapine) at that moment because of her hematological disease, since they can also decrease the number of thrombocytes (5). We decided to broaden the current therapy with an antipsychotic and benzodiazepine and to introduce lithium carbonate, as augmentation to the existing therapy (6).…”
Section: Case Reportmentioning
confidence: 99%